Developing creativity and curiosity outdoors how to extend creative learning in the early years - Johnson, Julie 1962-; Watts, Ann (Routledge, 2018)
"This accessible guide will inform, prompt and inspire practitioners as they develop their own creativity and seize the rich opportunities offered by outdoor environments to cultivate and encourage the creative skills of the young children in their care. Including information on Forest School, Developing Creativity and Curiosity Outdoors builds on theories of creative learning and development, and offers a wealth of ideas and activities for application in a range of outdoor settings."--Provided by publisher.